Effect of pH on phosphorylation of sago starch - Muhammad, K.; Hussin, F.; Man, Y.C.; Ghazali, H.M. (Elsevier Science, 2000)
Sago starch, in a semidry state was phosphorylated with 2% sodium trimetaphosphate (STMP), 5% sodium tripolyphosphate (STPP) singly, and in combination at pH levels between 6 and 11. As the reaction pH was increased from 6 to 11, the degree of phosphorylation was observed to decrease from 0.186 to 0.083% P with STPP, except at pH 9 where the degree of phosphorylation was increased to 0.224% P. In the case of STMP, the degree of phosphorylation increased from 0.066 to 0.119% P as reaction pH was increased from 6 to 10. In the reactions using a mixture of STPP and STMP, the P content decreased from 0.320 to 0.115% when a similar range of pH was employed. At the reaction pH of 9, a starch phosphate obtained using STPP exhibited low hot paste viscosity but high cold paste viscosity and shear stability when cooked at 95 °C. Treatment of sago starch with a mixture of STPP and STMP yielded the best starch phosphate at the reaction pH of 9.5 which showed lower hot paste viscosity and much higher cold paste viscosity than that of sago starch phosphates prepared at pH 9 using STPP. Paste clarity measurements of the phosphorylated starches indicated that cross-linking accelerated rapidly above pH 8 with STMP, above pH 9 with STPP, and above pH 6 with a mixture of the two.